ANALISIS STRATEGI PENGHIMPUNAN DANA INFAQ MELALUI PROGRAM SAFARI BERKISAH DI YAYASAN DANA SOSIAL AL FALAH MALANG - Puspita Sari, Anggie; Anggraini, Ika Khusnia (Islamic Economics and finance in Focus, 2024)
Many infaq management institutions such as Baznas and LAZ have been established. These institutions certainly need a strategy in collecting for the sustainability of the institution and realizing its distribution program. This study aims to determine the implementation of the Safari Berkisah program as a method of collecting infaq at YDSF Malang, and the impact of the Safari Berkisah program on YDSF Malang and stakeholders. The gap between this research and the research that has been done lies in the object of research where in previous studies no one has made Safari Berkisah as the object of research. The method used in this research is a qualitative method with a case study approach. From this research it is known that the implementation of the Safari Berkisah program at YDSF Malang is in accordance with the stages of fundraising strategy and the program has a positive impact on YDSF Malang and stakeholders. The results of this study are expected to be input for the Al Falah Social Fund Foundation Malang regarding the Safari Berkisah method as one of its collection methods, and can be taken into consideration for zakat, infaq, and alms management institutions in carrying out collection activities, especially through Safari Berkisah activities.